Microorganisms indicators the coliforms group in salmon sashimis marketed in the city of Mossoró, Rio Grande do Norte - Freire, Bárbara Camila Firmino; Soares, Karoline Mikaelle de Paiva; Santiago Filho, Paulo de Tarso de Paula; de Melo, Elisandra Cibely Cabral; Souza, Lara Barbosa de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The fish has been highlighted in national mart, beyond to receive new presentation forms, as is the case with sashimi. This has generated concern about high susceptibility to microbial contamination observed in the product. Based on this, the objective was to investigate microorganisms of the coliforms group in salmon sashimis, commercialized in the city of Mossoró, Rio Grande do Norte. Therefore, sashimi was corrected in specialized and non-specialized establishments in oriental food, obtaining twelve samples. The analyses consisted in the determination of microorganism of coliforms group and Escherichia coli confirmation. The obtained results showed contamination by thermotolerant coliforms above permitted by legislation, as well as the presence of E. coli in some samples, being this a probable indicative of fecal contamination during processing of salmon sashimi.